Detecting horizontal gene transfer among microbiota: an innovative pipeline for identifying co-shared genes within the mobilome through advanced comparative analysis - Schwarzerova, Jana; Zeman, Michal; Babak, Vladimir; Jureckova, Katerina; Nykrynova, Marketa; Varga, Margaret; Weckwerth, Wolfram; Dolejska, Monika; Provaznik, Valentine; Rychlik, Ivan; Cejkova, Darina (Microbiology spectrum, 2024)
Horizontal gene transfer (HGT) is a key driver in the evolution of bacterial genomes. The acquisition of genes mediated by HGT may enable bacteria to adapt to ever-changing environmental conditions. Long-term application of antibiotics in intensive agriculture is associated with the dissemination of antibiotic resistance genes among bacteria with the consequences causing public health concern. Commensal farm-animal-associated gut microbiota are considered the reservoir of the resistance genes. Therefore, in this study, we identified known and not-yet characterized mobilized genes originating from chicken and porcine fecal samples using our innovative pipeline followed by network analysis to provide appropriate visualization to support proper interpretation.
Keywords: genom bakteriální; mobilome; genome evolution; gut microbiota; Genes, Bacterial; mikrobiota; horizontal gene transfer; mobile genetic elements; resistance genes; Microbiota; antibakteriální látky; přenos genů horizontální; Gene Transfer, Horizontal; animal microbiome; zvířata; Swine; Anti-Bacterial Agents; bakteriální geny; Bacteria; Animals; Genome, Bacterial; prasata